Ben Burton: Born and Bred at Sea - Kingston, William Henry Giles, 1814-1880; Webb, Archibald, 1887-1944 (Salt Lake City, UT : Project Gutenberg, 2007)
"Ben Burton: Born and Bred at Sea" by William Henry Giles Kingston is a novel written in the late 19th century. This adventurous tale follows the life of Ben Burton, who grows from a newborn aboard a naval ship into a senior naval officer, detailing his experiences and adventures at sea, alongside a cast of characters including his parents and fellow sailors. The narrative captures the romance and danger of naval life during the age of exploration and conflict. At the start of the story, we are introduced to the ship "HMS Boreas" and the circumstances surrounding Ben's birth. The narrative sets up Ben's family dynamics aboard the ship, highlighting his mother Polly and the ship$1 (Bs company, who shower attention on the new arrival. The opening scenes depict various personalities, including the father$1 (Bs brave exploits, his mother$1 (Bs nurturing role, and Susan King, another woman aboard, who adds to the familial atmosphere. As Ben grows, he quickly becomes enamored with life on the ship, setting the stage for a series of nautical adventures that define his youth and character development. The stage is set for a rich journey filled with camaraderie, challenges, and the indomitable spirit of life at sea. (This is an automatically generated summary.)s
Release date is 2007-05-15
Produced by Nick Hodson of London, England
Keywords: Seafaring life -- Juvenile fiction